FIONA1‐Mediated m6A Modification Regulates the Floral Transition in Arabidopsis. Issue 6 (5th January 2022) - Xu, Tao; Wu, Xiaowei; Wong, Chui Eng; Fan, Sheng; Zhang, Yu; Zhang, Songyao; Liang, Zhe; Yu, Hao; Shen, Lisha
Abstract: N 6 ‐methyladenosine (m 6 A) mRNA modification represents the most widespread form of internal modifications in eukaryotic mRNAs. In the model plant Arabidopsis thaliana, those known methyltransferases mainly deposit m 6 A at their target transcripts near the stop codon or in the 3′ untranslated region. Here, it is reported that FIONA1 (FIO1), a human METTL16 ortholog, acts as a hitherto unknown m 6 A methyltransferase that determines m 6 A modifications at over 2000 Arabidopsis transcripts predominantly in the coding region. Mutants of FIO1 show a decrease in global m 6 A mRNA methylation levels and an early‐flowering phenotype. Nanopore direct RNA sequencing reveals that FIO1 is required for establishing appropriate levels of m 6 A preferentially in the coding sequences of a subset of protein‐coding transcripts, which is associated with changes in transcript abundance and alternative polyadenylation. It is further demonstrated that FIO1‐mediated m 6 A methylation determines the mRNA abundance of a central flowering integrator SUPPRESSOR OF OVEREXPRESSION OF CONSTANS 1 ( SOC1 ) and its upstream regulators, thus preventing premature flowering. The findings reveal that FIO1 acts as a unique m 6 A methyltransferase that mainly modifies the coding regions of transcripts, which underlies the key developmental transition from vegetative to reproductive growth in plants. Abstract : This work uncovers the function of FIONA1 as a unique m 6 A methyltransferase that mainly modifies the coding regions of transcripts, including those flowering‐related transcripts, to determine the transition from vegetative to reproductive development in plants. This study provides novel insights into understanding of m 6 A landscape, the associated new players, and their biological functions in plants.